2012
DOI: 10.1016/j.jfma.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging in the management of cervical cancer

Abstract: Positron emission tomography (PET), magnetic resonance imaging (MRI), and integrated 18-fluorodeoxyglucose ((18)F-FDG) PET/computed tomography are valuable techniques for assessing prognosis, treatment response after the completion of concurrent chemoradiation, suspicious or documented recurrence, unexplained post therapy elevations in tumor markers, and the response to salvage treatment when managing cervical cancer. However, PET plays a limited role in the primary staging of MRI-defined node-negative patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
0
7
0
3
Order By: Relevance
“…In the past decade, many studies have demonstrated the role of 18 Ffluorodeoxyglucose positron emission tomography (FDG-PET or PET-CT) in cervical cancer (9,10). FDG-PET might be superior to CT or MRI in determining lymph node status and distant metastasis (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, many studies have demonstrated the role of 18 Ffluorodeoxyglucose positron emission tomography (FDG-PET or PET-CT) in cervical cancer (9,10). FDG-PET might be superior to CT or MRI in determining lymph node status and distant metastasis (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Positron Emission Tomography (PET), a functional imaging modality, which utilizes radiotracers, mainly 18F-fluorodeoxyglucose (18F-FDG), along or combined with CT or MRI, to detect metabolic processes, is beneficial in cervical cancer for evaluation of primary disease status, nodal metastasis, distant metastasis, prognosis, and recurrence [1,2]. Kidd et al reported that prognostic nomograms composed with pretreatment 18F-FDG PET LN status, cervical tumor maximum standardized uptake value (SUVmax), and tumor volume could be a predictive model for recurrence free survival (RFS), diseasespecific survival (DSS), and overall survival (OS) [3].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…The prognosis is depended on International Federation of Gynecology and Obstetrics (FIGO) stage, histology, Lymph Node (LN) metastasis, lymphovascular space involvement, positive surgical resection margins [1]. Clinical staging by pelvic examination, imaging studies, mainly Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are widely used for pretreatment evaluation and detection of recurrences/ metastases.…”
Section: Introductionmentioning
confidence: 99%
“…To date no adequate evidence has been provided by a large scale or prospective study partly because of rareness of uterine sarcoma. In cervical cancer, radiotracers other than FDG such as 64 Cu-labeled diacetylbis(N4-methylthiosemicarbazone) ( 64 Cu-ATSM) were used to demonstrate hypoxia and 11 C-choline for proliferative activity, yet have not gained popularity [14].…”
Section: Pet Radiotracermentioning
confidence: 99%
“…Generally, International Federation of Gynecology and Obstetrics [FIGO] stages IA1-IIA1 diseases can be treated with either primary surgery or radiotherapy (RT), while stages IB2 to IV (except IIA1) diseases can be treated with definitive radiation with concurrent platinum-based chemotherapy [14]. MRI was found useful to confirm the absence of residual tumor in the cervix after a cone biopsy with negative margins in selection of patients for fertility-sparing radical trachelectomy [15].…”
Section: Clinical Staging Of Disease Extentmentioning
confidence: 99%